2017
DOI: 10.1186/s12969-017-0207-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk of tuberculosis among Alabama children and adolescents treated with tumor necrosis factor inhibitors: a retrospective study

Abstract: BackgroundTumor Necrosis Factor inhibitors (TNFi) have dramatically improved the outlook for patients with inflammatory arthritides and bowel disease (IBD), but are associated with increased infection risks, including tuberculosis (TB). Pediatric inflammatory diseases are uncommon, and the risk of TB in children taking TNFi remains unclear. The objective of this study was to report the incidence of TB disease among TNFi recipients at a single pediatric medical center serving most of Alabama compared to that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
1
3
0
2
Order By: Relevance
“…Our study highlights the great severity of TB disease in children on anti-TNF-α therapy, consistent with previous case reports [10,[13][14][15][16]. All patients captured by our study presented with severe disease.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study highlights the great severity of TB disease in children on anti-TNF-α therapy, consistent with previous case reports [10,[13][14][15][16]. All patients captured by our study presented with severe disease.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, fewer than 20 cases have been described in detail in the peer-reviewed literature so far [10][11][12][13][14][15][16]. Concerningly, several of those cases had a fatal outcome.…”
Section: Introductionmentioning
confidence: 95%
“…Few studies have been conducted since the implementation of tuberculosis screening to assess the incidence of tuberculosis among patients with rheumatoid arthritis, psoriasis or PsA. [24][25][26]29 We found a few cases of patients with treated tuberculosis in our cohort, four of whom were exposed to apremilast. The IRs for treated tuberculosis among users of DMARDs and biologics in our study fall within the range previously reported.…”
Section: Discussionmentioning
confidence: 69%
“…Zu Kindern und Jugendlichen liegen einzelne Fallberichte oder Ergebnisse kleiner Kohortenstudien vor, die auch über schwere und zum Teil letale Verläufe einer Tuberkulose unter einer Anti-TNF-a-Therapie berichteten 2225 . Die bisher größte Studie zu dem Thema der TNF-α-assoziierten Tuberkulose bei Kindern und Jugendlichen wurde kürzlich von der Paediatric Network European Trials Group (ptbnet), einem Netzwerk von Pädiatern, die in Europa im Bereich der Kindertuberkulose mit dem Fokus auf klinische Forschungsprojekte kooperieren, veröffentlicht 26 .…”
Section: Tuberkulose Unter Therapie Mit Tnf-α-inhibitorenunclassified